An unusual case of massive vaginal eversion complicated by obstructive uropathy - Sanyal, Urmi; P. B., Hiremath; Ghosh, Shilpa; N. R., Indu; M. R., Ramya; Hiremath, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Pelvic organ prolapse is the descent of the pelvic organs (uterus or bladder or rectum) from their normal anatomical position, in varying combination, into or beyond the vagina as a result of failure of the ligamentous and fascial supports. Sometimes the resulting vaginal eversion or protrusion is so massive it may cause outflow obstruction of one or both ureters. Here authors present a case of a 62 year postmenopausal woman having massive vaginal eversion leading to obstructive uropathy and chronic renal insufficiency. The prolapse was corrected by Sacrohysteropexy.